Diagnostic Efficiency of Heat Shocked Protoscoleces Extract Antigens for Human Cystic Echinococcosis by ELISA - Alsakee, Hadi M. A. (Iraqi Journal of Science, 2023)
Diagnosis of cystic echinococcosis is complex and has to be confirmed by the combination of immunological tests and imaging techniques. In this study heat shock proteins were induced and their immunoreactivity was assessed by ELISA.Sera were collected from 34 hydatid patients who were admitted to the Rizgary Teaching Hospital through October 2013 to July 2017, in addition to 29 healthy donors and 18 non-hydatid cases. For heat shock response, two batches of 25000 protoscoleces (Ps) were incubated separately at 42°C and 45 °C for 4 hours. Heat treated and normal Ps were disrupted and the extracts were divided into two parts. One part was directly used as source of antigens (PE, PE42 and PE45) and the other one was partially purified on Sephadex G150. The immunoreactivity of these antigens, as well as hydatid fluidwas assessed by ELISA. The cutoff value to differentiate positive from negative sera was established by receiver operating characteristic (ROC) analysis.Two peaks of PE42 and three peaks of PE45 resulted by Sephadex G150. Extracts of 42ºC treated Ps resulted in two protein peaks and were used as PE42P1 and PE42P2 antigens. For 45°C treated Ps, the chromatography patterns resulted in three protein peaks and were used as PE45P1, PE45P2 and PE45P3 antigens. Highest rates of sensitivity, specificity and diagnostic accuracy were detected with PE42P2 (91.2%) and PE45P2 (91.2%). Sensitivity of ELISA was consistent for liver cysts with all applied antigens.Hydatid antigens extracted from heat treated Ps markedly raised the sensitivity of ELISA to detect anti-hydatid IgG.